2006
DOI: 10.2478/s11658-006-0044-0
|View full text |Cite|
|
Sign up to set email alerts
|

Plant dehydrins — Tissue location, structure and function

Abstract: Dehydrins (DHNs) are part of a large group of highly hydrophilic proteins known as LEA (Late Embryogenesis Abundant). They were originally identified as group II of the LEA proteins. The distinctive feature of all DHNs is a conserved, lysine-rich 15-amino acid domain, EKKGIMDKIKEKLPG, named the K-segment. It is usually present near the C-terminus. Other typical dehydrin features are: a track of Ser residues (the S-segment); a consensus motif, T/VDEYGNP (the Y-segment), located near the N-terminus; and less con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
235
0
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(248 citation statements)
references
References 76 publications
(179 reference statements)
6
235
0
7
Order By: Relevance
“…These results suggest that the transgenic plants appear primarily to tolerate osmotic stress exerted by NaCl and mannitol. When plants are subjected to stress leading to cellular dehydration, a number of hydrophilic proteins like lateembryogenesis-abundant (Rorat 2006) and antifreeze proteins (Griffith and Yaish 2004) are induced or upregulated. The hydrophilic C-terminal of TrMADS3 implies the activity of the protein under dehydration conditions in Taihangia.…”
Section: The Expression Implication Of Trmads3 In Taihangiamentioning
confidence: 99%
“…These results suggest that the transgenic plants appear primarily to tolerate osmotic stress exerted by NaCl and mannitol. When plants are subjected to stress leading to cellular dehydration, a number of hydrophilic proteins like lateembryogenesis-abundant (Rorat 2006) and antifreeze proteins (Griffith and Yaish 2004) are induced or upregulated. The hydrophilic C-terminal of TrMADS3 implies the activity of the protein under dehydration conditions in Taihangia.…”
Section: The Expression Implication Of Trmads3 In Taihangiamentioning
confidence: 99%
“…They are found to accumulate in seeds during late embryogenesis, in plant tissues by stresses and processes leading to water deWcit, and responsive to the abscisic acid (e.g. Ingram and Bartels 1996;Campbell and Close 1997;Rorat 2006). They may play a role in the development of freezing tolerance and cold acclimation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Arabidopsis dehydrins ERD10 and ERD14 fulfill protective functions acting as potent chaperones of broad substrate specificity and they also have membrane-binding capacity (Kovacs et al, 2008). It was also reported that both ERD10 and ERD14 can be phosphorylated at various sites, which promotes the binding of divalent metal ions, and this might be related to their ion-sequestering activity (Rorat, 2006). Drought tolerance is assessed as the ability of plants to maintain a certain level of production under water shortage, which is relevant for most economically important crops (Volaire and Lelievre, 2001).…”
Section: Dehydrinsmentioning
confidence: 99%
“…Dehydrins belong to the group of Late Embryogenesis-Abundant (LEA) proteins which are expressed in late stages of seed maturation and/or upon water stress conditions in plants (Rorat, 2006). They constitute a highly divergent group of thermostable intrinsically disordered proteins that can be classified into different types according to the presence of distinct, short sequence motifs.…”
Section: Dehydrinsmentioning
confidence: 99%
See 1 more Smart Citation